Optimization for a hybrid energy storage system in electric vehicles using dynamic programing approach. (1st February 2015) - Song, Ziyou; Hofmann, Heath; Li, Jianqiu; Han, Xuebing; Ouyang, Minggao
Highlights: Dynamic programing approach is used to optimize the hybrid energy storage system. Components sizes and the system control strategy are optimized simultaneously. The life cycle cost of the system is rapidly reduced initially with SC increases. Four control rules are extracted from the DP results to obtain an on-line strategy. The on-line strategy performance can be further improved by increasing the SC usage. Abstract: This paper utilizes the dynamic programming (DP) approach to deal with the integrated optimization problem for deriving the best configuration and energy split strategies of a hybrid energy storage system (HESS), including a battery and a supercapacitor (SC), for an electric city bus. Within the optimization process, a preset cost function is employed to evaluate the HESS life cycle cost based on a dynamic degradation model of the LiFePO4 battery, which is initially proposed by us. For system hybridization, the battery size is optimized according to the requested minimal mileage, while the optimal configuration of the SC pack (i.e., the numbers of the SC modules in series and parallel) is determined using the DP approach. It is shown that the life cycle cost of the HESS initially decreases rapidly with the addition of SCs, though the rate of this reduction decreases as the amount of SC increases. The HESS candidates occurring in the transition area can therefore be regarded as the best solutions. For the energy split strategy, several control rules can be extracted from the DP results, and a near-optimal rule-based strategy is proposed in this paper. When compared to the battery-only configuration, the HESS controlled by the rule-based strategy can reduce 47% and 60% of the ESS life cycle cost along the typical China Bus Driving Cycle and the Urban Dynamometer Driving Schedule, respectively. This paper also proves that a well-tuned rule-based strategy, which can be easily implemented in a vehicle, presents rather good performance when compared to the DP approach. In addition, the proposed strategy performance can be further improved by increasing the SC usage.